NEURITIS OPTIK PADA SINDROM SJGREN - Winda Kusumadewi,* Darma Imran,* Riwanti Estiasari* (NEURONA, 2016)
NEURITIS IS KNOWN AS A NEUROLOGIC MANIFESTATION OF SYSTEMIC AUTOIMMUNE DISEASES PARTICULARLY IN SJGRENS SYNDROME COEXISTING SJGRENS SYNDROME HAS BEEN REPORTED IN 2 TO 30 OF PATIENTS WITH NEUROMYELITIS OPTICAOPTIC NEURITIS HAS BEEN ASSOCIATED WITH SJGRENS SYNDROME